Histopatologia em Astyanax bifasciatus (Garavello, 2010) como biomarcador para biomonitoramento de riachos com diferentes usos e ocupação do solo. - Nimet, Jardel (2016)
Abstract: This study evaluated the use of gill and liver of Astyanax bifasciatus as histological biomarkers for biomonitoring of streams with different uses and land occupation. The fish were collected by electric fishing technique, in six streams classified as afforested, rural and urban, in the basin of the lower Iguaçu River, west region of Paraná State, in December 2014. It was tested the hypothesis that in streams that are influenced by effluents from urban and rural areas occur greater number and histopathological severity in gill and liver of A. Bifasciatus. In this context, the objective of this study was to correlate the presence and degree of histopathology of gill and liver with the environmental variables among streams with different uses and land occupation. The environments considered afforested showed higher values of dissolved Oxygen (DO) and lower conductivity (CO) when compared to the rural and urban environments. The gills of fish from the afforested streams indicated normal functioning of the organ, while in the rural and urban streams, the histopathology in the gills suggested light to moderate damage to the organ. In relation to the liver, the histopathology indicated light to moderate damage in rural streams and moderate to severe damage in urban streams. When considering the abiotic variables and frequencies of histopathology of gill and liver, the afforested streams were separated from rural and urban areas. The histopathology in gills and livers were significantly more severe, corroborating our hypothesis. It was possible to distinguish streams with different uses and land occupation, therefore, these histopatologias showed favorable biomarkers for studies of biomonitoring